2000
DOI: 10.1002/1099-0690(200007)2000:13<2357::aid-ejoc2357>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity in Rubyrins: X-ray Structural Characterisation of Planar and Inverted Rubyrins

Abstract: Meso aryl rubyrins exhibit three different structures. A planar (7) and two unusual inverted structures [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Some varieties of heterorubyrins obtained by Chandrashekar and co-workers have presented different conformational flexibility and dynamics in solution (Scheme ) (see refs , , , ). It was found that the preferential conformation of the free base heterorubyrin strongly depends on the type of heteroatom and the type of meso -substituents.…”
Section: Hexaphyrinsmentioning
confidence: 87%
See 1 more Smart Citation
“…Some varieties of heterorubyrins obtained by Chandrashekar and co-workers have presented different conformational flexibility and dynamics in solution (Scheme ) (see refs , , , ). It was found that the preferential conformation of the free base heterorubyrin strongly depends on the type of heteroatom and the type of meso -substituents.…”
Section: Hexaphyrinsmentioning
confidence: 87%
“…At low-temperature limits, dithiarubyrin 53 - 2 and oxathiarubyrin 53 - 5 exist in solution in inverted conformations, while diselenarubyrin 53 - 3 and ditellurarubyrin 53 - 4 prefer a normal geometry with all the heteroatoms pointing into the cavity. Interestingly, tetramesityldioxarubyrin 53 - 6 adopts a conformation with two inverted pyrrole rings (Scheme ), as established by 1 H NMR at −50 °C.…”
Section: Hexaphyrinsmentioning
confidence: 99%
“…1,2 From a structural perspective, expanded porphyrins with meso aryl substituents show a rich structural diversity where one or more heterocyclic rings exhibit an unusual 180 • ring flipping leading to partially inverted structures, including N-confused macrocycles. 9,10 Reactivity studies mostly have concentrated on studying the ability of these macrocycles to bind anions and cations. Expanded porphyrins in their free base form have affinity for transition metal cations 1,2 while in their protonated form they bind anions.…”
Section: Chartmentioning
confidence: 99%
“…9 Three different types of structures have been observed for meso aryl rubyrins both in solution and in solid state. 10 …”
Section: Scheme 10mentioning
confidence: 99%
See 1 more Smart Citation